Carbogen treatment for pH-stat management in cardiopulmonary bypass / Vijay Sundra Kumuran - Sundra Kumuran, Vijay (2012)
Hypocarbia commonly occurs in infants undergoing cardiopulmonary bypass causing respiratory alkalosis with pH-stat management. In this study, pCO2 regulation was adjusted accordingly to sweep gas in control and treatment groups with gas-to-blood flow ratio of 0.5:1. Each extracorporeal membrane oxygenator (Capiox® RX05 and Medtronic® Minimax Plus® Hollow Fiber Oxygenator) contained control and treatment groups to determine carbogen intervention is necessary for infants undergoing hypothermic bypass. Arterial blood gas was corrected according to actual temperature of the patients for both control (without carbogen) and treatment (with carbogen) groups. The carbogen treatment was introduced to overcome the problem of maintaining pH and pCO2 for infants undergoing hypothermic bypass. One hundred and twenty (120) infants